PERANCANGAN APLIKASI TRANSAKSI PENJUALAN PULSA BERBASIS DESKTOP DAN MOBILE - Rizky, Adrianus (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Application of credit sales transactions based desktop and mobile is one important thing in doing a simcard komunikasi.Registrasi assist in the activation numbers to input data in accordance with a valid identity dsn done by the seller in addition to the business transactions of this pulse is needed by all communities the recharging pulse. These applications replace the old system in which frequent errors against inaccuracies in the process of inputting data manually. The purpose of making this application is to record transaction processing and presentation of transactions accurately, quickly, and efficiently. This system is not only equipped with computer, but comes with sales reports that can be printed when needed in a time period of one month or more. This application was built using Visual Basic 2012 programming and android studio as well as using SMS Gateway online, while for the MySQL database. The sales registration data and also entered in the database storage